Prevalence and Frequency of Congenital Anomalies in Al - Rifai Teaching Hospital (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Background: Congenital anomalies define as abnormalities of body structure that originated before birth, about 3% of all children are born with a serious structural defect that interferes with normal body function and can lead to lifelong handicap or even early death. There is a variation in the frequency of congenital anomalies in different populations.Aim of study: To identify the most common types of congenital abnormalities and their percentage among newborn infants in neonatal care unit in Al - Rifai teaching Hospital, And To identify the probable predisposing factors that result in these congenital abnormalitiesPatient and Method: This was a retrospective study performed in Al - Rifai teaching Hospital at the neonatal care unit (which serves both urban and rural area) in a period from the 1st of January 2010 to the 31th of December 2014. The total number of deliveries was 50917 live birth. From all these deliveries, there were 670 with gross congenital anomalies where evaluated by pediatrician in the neonatal intensive care unit..Result: 670 cases had have a gross congenital anomalies. The average of Prevalence during five years was 1.3% with high incidence during 2019.this study showing male predominance and the most affected system was CNS 255(33.6) fallowed by SYNDROMES 245(32.3),GIT 80(10.5) RENAL 67(8.8) MUSKELOSKELETAL 60(7.9)and lastly RESPIRETORY 50(6.6).the affected maternal age was between 20-30 years. Body weight consanguinity and maternal risk factor like chronic disease drugs exposure and radiation had important role.Conclusion: Neurological anomalies, especially neural tube defects, are the most common type of congenital abnormalities in newborn infants with CNS relatively higher male than female infants. Fallowed by syndromes especially (down syndrome).